Effect of age on the relative efficacy of clozapine in schizophrenia. (13th June 2020) - Jones, R.; MacCabe, J.H.; Price, M.J.; Liu, X.; Upthegrove, R.
Abstract : Objective: Early treatment of schizophrenia improves outcomes. Clozapine appears to have unique benefit when other antipsychotic medication has failed. This systematic review and meta‐analysis aims to assess clozapine's superiority over alternative antipsychotic medication and examine whether earlier use is associated with additional benefit. Method: Systematic retrieval of blinded, randomized controlled trials comparing clozapine with alternative antipsychotics in adults with schizophrenia. The effect of mean age on relative clozapine response was examined using random effects meta‐regression, and multiple linear regression on available patient data. Results: A total of 276 studies were retrieved. Thirty‐four studies were included in the meta‐analysis. Clozapine was significantly more effective than alternative antipsychotics in reducing psychotic symptoms and increasing response. However, meta‐regression failed to show a more significant effect in younger patients (age on effect size (total psychotic symptoms) 0.00, P = 0.79 CI −0.03 to 0.03). Individual patient data were available for two studies, the larger of which showed a significant interaction between younger age and superiority of clozapine. Conclusion: The results support clozapine's superiority over other antipsychotics. A convincing effect of age on this effect was not demonstrated, although this was suggested in one study. In view of the age of many of the included studies, and changes in reporting practice over time, new clozapine RCTs, which include age of illness onset as well as age at trial time, would be welcome in order to provide meta‐analysable data for future use.